Allergen‐specific subcutaneous immunotherapy for Japanese cedar pollinosis decreases the number of metachromatic cells and eosinophils in nasal swabs during the preseason and in season. Issue 3 (2nd April 2020) - Otsuka, Kuninori; Otsuka, Hirokuni; Matsune, Shoji; Okubo, Kimihiro
Abstract: Background and objective: Nasal symptoms of allergic rhinitis can be reduced with allergen‐specific subcutaneous immunotherapy (SCIT). However, the mechanisms underlying the effectiveness of SCIT for Japanese cedar pollinosis are not well understood. We studied changes in the numbers of metachromatic cells, eosinophils and neutrophils in nasal swabs following SCIT for Japanese cedar pollinosis. Methods: Subjects were either untreated or given SCIT for 0.5 to 13 years duration. For the 2019 seasons, nasal swabs were taken in the pollinosis preseason (immunotherapy n = 36; untreated control, n = 62) and in the pollinosis season (immunotherapy n = 45; untreated control n = 46) and the numbers of mast cells, eosinophils and neutrophils assessed by microscopy. Results: There were significant improvements in symptom severities following SCIT in comparison to untreated subjects ( P < .0003, the Mann‐Whitney U test) in preseason, and ( P < .00001) in season. Metachromatic cell counts from nasal swabs of SCIT subjects in preseason and in the season were lower than those of untreated subjects ( P = .0029 and P = .031, respectively). Eosinophil numbers in nasal swabs of subjects given SCIT were lower than in untreated subjects ( P = .0031) in season, but not in preseason. There were no significant differences in degrees of neutrophilia between untreated and SCIT subjects in preseason and in season. Conclusion: One mechanism underlying the effectiveness of SCIT for Japanese cedar pollinosis involves a reduction in the number of metachromatic cells in nasal swabs in the preseason and an inhibition of increases in the number of metachromatic cells and eosinophils in season. Abstract : The number of metachromatic cells in nasal swabs in untreated subjects (B) and SCIT (C) for Japanese cedar pollinosis in pre‐season and in season.